Construction Management Modeling in Partnership Governance of Laboratory Building Projects - Hariyani, Betty; Koespiadi, Koespiadi; Setiawan, M. Ikhsan (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
Construction management is a crucial aspect in the governance of building construction project partnerships. The complexity and challenges in building construction projects, such as multi-stakeholder involvement, uncertainty, and time and cost pressures, signal the importance of the construction management role. Good partnership governance can help address these challenges by improving transparency, accountability, and communication between parties. This study aims to find a partnership management model in determining the best vendors in the implementation of the Biosafety Level (BSL) 2 Building Construction project and describe the proposed partnership management model in determining the best vendors in the implementation of the BSL 2 Building Construction project. This research is a research on dynamic system methods through the development of simulation models with the help of Powersim studio 10 software. The research was carried out at PT. Nella Putri Banjaran KSO PT. Bettindo Bintang Perkasa. Data were collected through field studies and literature studies. The results of the study show a significant trend of increasing delays in the supply of raw materials and project costs, it can be concluded that there are fundamental problems in project management. Persistent delays in the supply of raw materials indicate obstacles in project planning, implementation, or supervision. Solid partnerships between the various parties involved in the project, such as project owners, contractors, consultants, and subcontractors, can be key in addressing these issues. The partnership management model in determining the vendor for the implementation of the BSL 2 building construction project by reducing the average delay in the supply of project raw materials, improving project time management, reducing the average increase in project costs by improving project cost management. Through long-term agreements, joint planning, and effective monitoring mechanisms, supply delays can be minimized.